Pengaruh Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan (PNPM-MP) dalam Upaya Pemberdayaan Usaha Ekonomi Masyarakat Pedesaan - Samie L Jacobs; Jondry A Hetharie (Jurnal Ilmiah Aset, 2012)
National Program of Empowerment of Self-Supporting Countryside Society (PNPM-MP) launched as the follow-up of anticipaty program of poorness and empowerment of previous society like Program of Inpres Countryside Left Behind ( IDT), Empowerment Program Of Society Affect Economic Crisis (PDM-DKE) with program emphasis at empowerment of society and empowerment of institute in district storey; level/ countryside and canton. National Program of Empowerment of Self-Supporting Countryside Society (PNPM-MP) as continuation to Program of Inpres Countryside Left behind, development of countryside coordinated by Directorate Generaling Countryside Development for example having goals qualitative and quantitative like activity in the form of capital employed aid and is ready of medium and infrastructure which supporting productive economic activity [pass/through] institute in district storey;level and countryside. National Program of Empowerment of Self-Supporting Countryside Society (PNPM-MP) represent study media to government officer and society activity of transparent and democratic decision making, goodness in the plan, execution and continuation of activity program.